Infrastructure sharing and access to broadband: the role of policy and regulation - Magagane, Mankakane Violet (My University, 2013)
ABSTRACT Infrastructure sharing is seen an opportunity to reduce the costs of deploying infrastructure and of gearing investment towards underserviced areas. It has since emerged that there is duplication and concentration of infrastructure in urban areas and limited infrastructure in many parts of the country. This complicates the sharing of infrastructure and the effectiveness of the infrastructure sharing instruments on essential facilities, facilities leasing and interconnection regulations in granting access to a wide range of services such as voice and broadband. The purpose of this study is to explore policy and regulatory instruments in infrastructure sharing and access to broadband. The study took into account the literature on policy and regulation and infrastructure sharing, the industry views and considered the trends in infrastructure sharing and the provision of ubiquitous networks to underserviced areas. The study found that network infrastructure sharing has the potential of providing the rapid development of access infrastructure capable of handling high bandwidth requirements suitable for an information society.
Dissertation submitted to the faculty of Commerce, Law and Management, University of the Witwatersrand, in fulfilment of the requirements for the degree of Master of Management in ICT PR
Keywords: Broadband; South Africa; Telecommunication policy